ADENOCARCINOMA EN CÉLULAS EN ANILLO DE SELLO UN RARO SUBTIPO DE CÁNCER DE VESÍCULA BILIAR (Revista Argentina de Cirugía, 2022)
GaIIbIadder carcinoma is the most common tumor of biIe ducts. They are mostIy adenocarcinomas. The signet ring ceII carcinoma is a rare subtype of which have been pubIished onIy 10 cases. We present a case of a 38-year inciden- taI T2N2 carcinoma without invoIvement of neighboring organs that despite adequate surgery and chemotherapy with good initiaI response died at 8 months after surgery. Is need more experience in managing and monitoring of these tumors.
Keywords: Gallbladder; neoplasm